PHONOLOGICALERRORS BETWEEN JAVANESE AND SUNDANESE OF BILABIAL AND LABIO-DENTAL SOUNDS IN TONGUE TWISTERACTIVITY - Wika Putri Lapusza; Yunita Yunita; Isry Laila Syatroh (PROJECT (Professional Journal of English Education), 2019)
Much attention has been paid on the phonological errors in tongue twister activity of Javanese and Sundanese people. In Indonesia, every single area has different pronunciation dialects, especially Javanese and Sundanese. Javanese is famous with “medok”. It is the Javanese dialect which is powerful when spelling P and B. Some Sundanese people find it difficult to spell F and V. For example when speaking “of”, Sundanese usually says “op”. The aim of this paper to prove assumption about Javanese people who are famous with medok sounds and for Sundanese people having difficulties to says f and v. The writers use qualitative method, with descriptive qualitative design. This paper uses purposive sampling design. For the participants the writers choose fifth semesters students of IKIP Siliwangi Bandung aged twenty until twenty-one years old. The samples are five Javanese people and five Sundanese people (four males and six females). The result of this research for Javanese people have 57% phonological errors of bilabial sounds and for Sundanese people have 59% phonological errors of labio-dental sounds. The result of this study supports people’s assumption about phonological errors made by Javanese and Sundanese people in producing bilabial and labio-dental sounds.